2017
DOI: 10.1002/ceat.201600719
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Solution Composition and Polymer Additive on the Crystallization of Struvite

Abstract: Reject water from a wastewater treatment plant contains a large amount of phosphorus that can be recovered and used as phosphate fertilizer. However, the quality of the final products is affected by the variation of wastewater composition. This work focuses on the effects of the nitrogen/phosphorus (N/P) molar ratio, which is a mutable variable in the reject water, and a polymer additive on the crystallization of struvite from an artificial reject water system. The obtained results suggest that crystallization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Biological and/or chemical treatment procedures are necessary to meet the discharge limit set by political regulations (de- Bashan and Bashan, 2004). Phosphate recovery/recycling by controlled precipitation of struvite and calcium phosphate precipitation, which remove phosphate from the liquid phase after sludge dewatering, do not exploit the full potential for phosphate recovery (Liu and Qu, 2017;Song et al, 2006;Vasenko and Qu, 2017). Thus, the sludge contains valuable phosphate, but the direct application of sludge to fields is problematic as toxins such as heavy metals, microplastic, and pathogens may be present in critical quantities.…”
Section: Introductionmentioning
confidence: 99%
“…Biological and/or chemical treatment procedures are necessary to meet the discharge limit set by political regulations (de- Bashan and Bashan, 2004). Phosphate recovery/recycling by controlled precipitation of struvite and calcium phosphate precipitation, which remove phosphate from the liquid phase after sludge dewatering, do not exploit the full potential for phosphate recovery (Liu and Qu, 2017;Song et al, 2006;Vasenko and Qu, 2017). Thus, the sludge contains valuable phosphate, but the direct application of sludge to fields is problematic as toxins such as heavy metals, microplastic, and pathogens may be present in critical quantities.…”
Section: Introductionmentioning
confidence: 99%
“…A high concentration of the struvite-forming ions in the inlet-mixed solution can shift the solid−liquid equilibrium to a lower pH. 20,72 The calculated saturation index for experiment L9 M was already higher than zero (0.9) at pH 6.0. This finding indicates the potential of struvite precipitation at a pH lower than 9.0 in the case of HTL byproducts of manure, corresponding with the observation from the experiment.…”
Section: Effect Of Inlet-mixed Solution Composition On Htl-based Stru...mentioning
confidence: 95%
“…Struvite precipitation is widely applied to recover phosphate and/or nitrogen from municipal, farm, and agro-industrial wastes, and the literature regarding the effect of operating parameters on the struvite precipitation from these wastes is extensive; for example, effects of temperature and pH are summarized in reviews. , The molar ratio of the struvite-forming ions in the solution also has a significant effect. Experimental studies on struvite precipitation from solutions of different complexities have indicated that increasing the ammonium-to-phosphate ion molar ratio and the magnesium-to-phosphate ion molar ratio over 1:1 favors struvite formation. The presence of non-struvite-forming constituents in the solution (denoted as foreign ions) can influence both the thermodynamics and kinetics of struvite precipitation, which affects the properties of the precipitate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the aquatic life is threatened and the water bodies becomes unsightly and unhealthy. The wastewater streams, especially those originating from household, agricultural and animal farming, are characterized by a high level of ammonia and P contents (Liu & Qu, 2017;Mpountas et al, 2017;Deng et al, 2006). Therefore, the effluents must be treated before discharging them into water bodies.…”
Section: Introductionmentioning
confidence: 99%